NarK enhances nitrate uptake and nitrite excretion in Escherichia coli. - DeMoss, J A (1991)
narK mutants of Escherichia coli produce wild-type levels of nitrate reductase but, unlike the wild-type strain, do not accumulate nitrite when grown anaerobically on a glucose-nitrate medium. Comparison of the rates of nitrate and nitrite metabolism in cultures growing anaerobically on glucose-nitrate medium revealed that a narK mutant reduced nitrate at a rate only slightly slower than that in the NarK+ parental strain. Although the specific activities of nitrate reductase and nitrite reductase were similar in the two strains, the parental strain accumulated nitrite in the medium in almost stoichiometric amounts before it was further reduced, while the narK mutant did not accumulate nitrite in the medium but apparently reduced it as rapidly as it was formed. Under conditions in which nitrite reductase was not produced, the narK mutant excreted the nitrite formed from nitrate into the medium; however, the rate of reduction of nitrate to nitrite was significantly slower than that of the parental strain or that which occurred when nitrite reductase was present. These results demonstrate that E. coli is capable of taking up nitrate and excreting nitrite in the absence of a functional NarK protein; however, in growing cells, a functional NarK promotes a more rapid rate of anaerobic nitrate reduction and the continuous excretion of the nitrite formed. Based on the kinetics of nitrate reduction and of nitrite reduction and excretion in growing cultures and in washed cell suspensions, it is proposed that the narK gene encodes a nitrate/nitrite antiporter which facilitates anaerobic nitrate respiration by coupling the excretion of nitrite to nitrate uptake. The failure of nitrate to suppress the reduction of trimethylamine N-oxide in narK mutants was not due to a change in the level of trimethylamine N-oxide reductase but apparently resulted from a relative decrease in the rate of anaerobic nitrate reduction caused by the loss of the antiporter system.